P-040. Direct-acting antiviral drugs used ın the treatment of HCV Increase cholesterol levels - Ozdogan, Osman (Turk J Gastroenterol, 2019)
INTRODUCTION: Aim is to investigate the effects of direct-acting antiviral (DAA) drugs on insulin resistance and lipid parameters in HCV treatment. METHODS: A total of 121 patients were included in the study. Fasting blood glucose (FBG), insulin level (insulin), insulin resistance, total cholesterol, HDL, LDL cholesterol and triglyceride levels were measured at 0, 1, 3, 6 and 12 months. RESULTS: HCV RNA levels were 3.394×103 ± 9.419×103 (min; 1255, max; 82.000 ×103) IU/mL. 117 patients were genotype 1. According to months, FBG levels were 96 ± 12, 102 ± 17, 100 ± 15, 100 ± 14, 100 ± 14 mg/dL, and HOMA-IR was 2.93 ± 0.96, 4.73 ± 2.69, 4.6 ± 2.07, 3.38 ± 2.33, 3.17 ± 1.58, respectively. Especially, at the 1st month of the treatment, insulin and HOMA-IR levels were significantly higher than the initiation of treatment (p <0.05). At the third month of treatment, this elevation continued, but it was observed that at the end of the treatment and at the end of the treatment it decreased to the initial values. It was found that total cholesterol and LDL cholesterol levels increased significantly in the first month of treatment (p <0.05) and this elevation persisted as high during the treatment and after the end of the treatment. Slight increase in triglycerides and HDL was not statistically significant (p >0.05). CONCLUSION: DAA drugs used in the treatment of HCV infection increased IR, total cholesterol and LDL cholesterol levels during treatment